VD_FINDINFO AP / 2013 / 23 vom 3. Januar 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS, ASSISTANCE JUDICIAIRE, RADIATION DU RÔLE | 109 al. 1 CPC (CH), 109 CPC (CH), 122 al. 1 let. a CPC (CH), 122 al. 1 let. b CPC (CH), 122 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 241 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)